Influence of detector motion in Bell inequalities with entangled fermions - Landulfo, Andre G. S. [UNESP]; Matsas, George Emanuel Avraam [UNESP] (Amer Physical Soc, 2009)
We investigate how relativity influences the spin correlation of entangled fermions described by wave packets and measured by moving detectors. In particular, we show that the Clauser-Horne-Shimony-Holt (CHSH) Bell inequality is not violated by quantum mechanics when the left and right spin detectors move fast enough. We also show that the violation of the Bell-CHSH inequality measured by the moving detectors decreases with increasing width of the initial wave packet.
Keywords: fermion systems; matrix algebra; quantum entanglement